The Difference a Year Can Make: How Antibiotic Resistance Mechanisms in Pseudomonas aeruginosa Have Changed in Northwestern Transylvania - Matei-Ștefan Dobrescu; Dan-Alexandru Țoc; Adrian-Gabriel Pană; Carmen Costache; Anca Butiuc-Keul (Biomolecules)
This study examines the prevalence and the mechanisms of antibiotic resistance in Pseudomonas aeruginosa isolates collected from healthcare units in Northwestern Transylvania, Romania, between 2022 and 2023. Given the alarming rise in antibiotic resistance, the study screened 34 isolates for resistance to 10 antibiotics, 46 ARGs, and integrase genes using PCR analysis. The results reveal a concerning increase in multidrug-resistant (MDR) and extensively drug-resistant (XDR) isolates over the two-year period. Notably, the prevalence of ARGs encoding resistance to sulfonamides and beta-lactams, particularly sul1 and blaOXA-50, has shown a significant rise. Furthermore, the study detected the emergence of new resistance mechanisms in the same time interval. These include target protection and even more specific mechanisms, such as metallo-beta-lactamases or enzymes involved in the methylation of 23S rRNA. Statistical analysis further confirmed the correlation between Class I integrons and several ARGs, underscoring the role of horizontal gene transfer in the dissemination of resistance. These findings emphasize the urgent need for updated treatment strategies and monitoring programs to effectively combat the spread of ARGs in clinical settings.